Distribution and gender effects on the path of economic growth: Comparative evidence for developed, semi-industrialized, and low-income agricultural economies - Ruth Badru (Levy Economics Institute of Bard College, 2020)
This paper applies a robust empirical methodology, which considers issues relating to cross-country heterogeneity and cross-sectional dependence, to inspect the contributions of gender equality and factor income distribution to an economy's growth path. A dynamic model of aggregate demand is estimated on a unique panel dataset from 46 countries that are further grouped into developed (DC), semi-industrialized (SIEs), and low-income agricultural economies (LIAEs). The empirical findings suggest that, overall, growth is driven by investment in the short run and domestic demand in the long run. In the short run, the results suggest that low female wages act as a stimulus to growth in SIEs but may promote contractionary pressures on demand in the long run. For LIAEs and DCs, the effect of improved labor market conditions for women-leaving men's constant-on demand-led growth conditions are positive in the short run but may harm long-term growth prospects. In all, the empirical evidence, combined with the stylized facts about institutional and economic inequality, suggests that the impact of gender and income inequality on macroeconomic outcomes will differ depending on the economic structure and level of economic development.
Keywords: E02; E12; E20; F41; I30; J03; J07; 330; Gender Equality; Demand-led Growth; Aggregate Demand; Functional Income Distribution; Economic Development; Autoregressive Distributed Lag Models (ARDL)